Choosing to study geography and the career aspirations of future graduates and postgraduates - Resnik Planinc, Tatjana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2023)
Several factors are bound to influence a young person’s decision to study a particular study programme, including his or her interests and commitment, abilities and skills, career prospects, family expectations, social pressure and peer influence, the information and advice available to him or her and financial constraints. To find out what factors contribute to adolescents’ decision to study geography and the career aspirations of future graduates and postgraduates, a survey was conducted in 2017 and 2020 at the Department of Geography, Faculty of Arts, University of Ljubljana involving a total of 155 students in their first year of the first cycle and the first and the second year of the second cycle. The results will be of great help in the further development of the geography study, as knowledge of the factors influencing their decisions to study, as well as their career aspirations and expectations, will allow us to understand the low enrolment figures in geography studies in recent years (which are not comparable to those of the past in all three Slovenian departments of geography) and to find po-tential solutions or ways to improve the current situation.
Keywords: career aspirations; geographical education; geography studies; poklicne aspiracije; Slovenia; Slovenija; šolska geografija; študij geografije